2017
DOI: 10.1186/s12890-017-0498-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sivelestat sodium in patients with acute lung injury or acute respiratory distress syndrome: a meta-analysis of randomized controlled trials

Abstract: BackgroundSivelestat is widely used in treating acute lung injury (ALI)/acute respiratory distress syndrome (ARDS), although the clinical efficacy of sivelestat remains controversial. This study aimed to evaluate the impact of sivelestat in patients with ALI/ARDS.MethodsElectronic databases, PubMed, Embase, and the Cochrane Library, were searched to identify trials through April 2017. Randomized controlled trials (RCTs) were included irrespective of blinding or language that compared patients with and without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Mice deficient in NE are more susceptible to Gram‐negative bacteria, suggesting that NE are required for adequate host defence against invading pathogens and complete inhibition of NE can be harmful . Despite data from preclinical models, sivelestat, a selective NE inhibitor, did not alter 28‐day mortality in a number of clinical trials (Table ) . Although alteration in oxygenation has been observed, the small sample sizes of the majority of clinical trials and heterogenous patient populations potentially mask any benefit in subgroups of patients with ARDS .…”
Section: Granule Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice deficient in NE are more susceptible to Gram‐negative bacteria, suggesting that NE are required for adequate host defence against invading pathogens and complete inhibition of NE can be harmful . Despite data from preclinical models, sivelestat, a selective NE inhibitor, did not alter 28‐day mortality in a number of clinical trials (Table ) . Although alteration in oxygenation has been observed, the small sample sizes of the majority of clinical trials and heterogenous patient populations potentially mask any benefit in subgroups of patients with ARDS .…”
Section: Granule Proteinsmentioning
confidence: 99%
“…Despite data from preclinical models, sivelestat, a selective NE inhibitor, did not alter 28‐day mortality in a number of clinical trials (Table ) . Although alteration in oxygenation has been observed, the small sample sizes of the majority of clinical trials and heterogenous patient populations potentially mask any benefit in subgroups of patients with ARDS . It is difficult to separate challenges in clinical trial design from limitations of biological importance in this context.…”
Section: Granule Proteinsmentioning
confidence: 99%
“…The injection of exosomes isolated from the serum of LPS-challenged mice increased the number of total and M1 macrophages and the levels of TNF-α and IL-6 in the lungs, which was associated with the increase of miR-155 (52). Although ARDS has attracted clinical attention for decades, none of the proposed therapies for ARDS including sivelestat sodium, neutrophil elastase inhibitor, have yet to show its clinical effect sufficiently (64). We might have overlooked the significance of exosomes as they cause inflammatory response and cell death in lungs independent of neutrophil activity (30,52).…”
Section: Lungsmentioning
confidence: 99%
“…A meta-analysis of 6 RCTs reporting data on 804 patients with ARDS showed that sivelestat might increase the PaO 2 /FiO 2 level, but with little or no effect on 28–30 days mortality, ventilation days, and ICU stays [ 90 ].…”
Section: Neutrophil Elastase Inhibitorsmentioning
confidence: 99%